Tipping the scales: overcoming obstacles to support school readiness for all in low- and middle-income countries. Issue 3 (3rd July 2019) - Spier, Elizabeth; Leenknecht, Frederik; Carson, Kaitlin; Bichay, Krystal; Faria, Ann-Marie
ABSTRACT: Despite evidence for the substantial benefits of school readiness among children in low- and middle-income countries (LMICs), most lack access to any pre-primary education at all, let alone high- quality preprimary education. In this article, we discuss obstacles and example of solutions to providing universal access to high-quality preprimary education in LMICs. We address (1) the need for a vision among policymakers, educators and families of what high-quality preprimary education should look like and how it could be provided in their context, and the motivation to make the vision a reality; (2) human resources, including motivated, skilled and qualified teachers as the center of a broad support system at national, regional and local levels; (3) material resources and infrastructure, including culturally appropriate play materials and child-friendly spaces; and (4) stable financing that allows for flexible adaptations of the model to different local contexts. For each element, we provide examples of these challenges and how they can be addressed, with a geographical focus on West Africa, the Middle East, Southern and Eastern Asia.